2009
DOI: 10.1007/s00442-009-1434-6
|View full text |Cite
|
Sign up to set email alerts
|

Saprotrophic capabilities as functional traits to study functional diversity and resilience of ectomycorrhizal community

Abstract: In an accompanying editorial Dr Petr Baldrian made a case casting doubt on our recent work addressing the saprophytic potential of ectomycorrhizal (EM) fungi. Dr Baldrian's statements illustrate a very valid truth: the book is still very much open on this subject. The point he raised that the only logical reason for these fungi to be responding to high carbon demand or decreased host photosynthetic capacity by up-regulating enzymes is for the purpose of carbon acquisition is valid as well. Despite this, he mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 31 publications
0
43
0
1
Order By: Relevance
“…ECM fungal community composition can be strongly structured by deterministic processes (Bruns 1995;Koide et al 2011), and some ECM fungal species have been detected in discrete soil niches (Tedersoo et al 2003(Tedersoo et al , 2008Buée et al 2007;Iwań ski and Rudawska 2007). Specialist wood decomposers are well characterized (Tanesaka et al 1993;Fukami et al 2010), but specialization for woody microsites by ECM fungi is equivocal (Talbot et al 2013;Walker and Jones 2013), despite the potential wood-degrading enzymatic capabilities of ECM fungal root tips (Talbot et al 2008;Cullings and Courty 2009). Because extramatrical fungal mycelia explore the substrate and subsequently colonize potential nutrient patches (Finlay and Read 1986), studies targeting ECM fungal hyphae may reveal stronger niche development as compared with root tips.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…ECM fungal community composition can be strongly structured by deterministic processes (Bruns 1995;Koide et al 2011), and some ECM fungal species have been detected in discrete soil niches (Tedersoo et al 2003(Tedersoo et al , 2008Buée et al 2007;Iwań ski and Rudawska 2007). Specialist wood decomposers are well characterized (Tanesaka et al 1993;Fukami et al 2010), but specialization for woody microsites by ECM fungi is equivocal (Talbot et al 2013;Walker and Jones 2013), despite the potential wood-degrading enzymatic capabilities of ECM fungal root tips (Talbot et al 2008;Cullings and Courty 2009). Because extramatrical fungal mycelia explore the substrate and subsequently colonize potential nutrient patches (Finlay and Read 1986), studies targeting ECM fungal hyphae may reveal stronger niche development as compared with root tips.…”
Section: Introductionmentioning
confidence: 98%
“…Fungal saprotrophs break down complex forms of dead organic matter, including wood, and biotrophic mycorrhizal fungi provide their host plants with mineral nutrients such as nitrogen (N) and phosphorus (P) (Lindahl et al 2007;Smith and Read 2008). Ectomycorrhizal (ECM) fungi may also play a role in decomposition (Talbot et al 2008;Cullings and Courty 2009) and have been shown to translocate photosynthesis-derived carbon (C) into the soil (Jones et al 1991;Clemmensen et al 2013) and to other plants (Finlay and Read 1986). Although much work has been done on enzyme activities associated with ECM fungal root tips (Buée et al 2007;Jones et al 2012), enzyme production and nutrient absorption occur primarily in the extramatrical ECM fungal hyphae (Agerer 2001;Genney et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests differences in carbon use between ECM species. Although there is some debate on the saprotrophic capacities of ectomycorrhizae (Baldrian 2009) it is reasonable to assume that there is a biotrophic-saprotrophic continuum in ECM fungi as summarised and discussed by Koide et al (2008) and Cullings and Courty (2009). Especially those ECM types with extensive mycelia are candidates to search for saprotrophic capacities and uptake of carbon from litter in parts of their mycelia remote from the carbon supply of their plant host.…”
Section: Introduction 2 Ectomycorrhizal Fungi and Nutrient Exploitationmentioning
confidence: 99%
“…The recent development of new methods for determining the potential enzymatic activity profiles of individual ECMs makes possible to decipher trait diversity of ECM communities (Courty et al 2005). Activities of extracellular enzymes can be considered as functional traits to study functional diversity and resilience of ectomycorrhizal community (Cullings and Courty 2009). The first applications of this novel approach (e.g., Courty et al 2005Courty et al , 2007Buée et al 2007;Rineau and Garbaye 2009b;Jones et al 2010) have revealed that the activity profile of ECMs formed by the same species may change significantly according to everchanging ecological conditions (i.e., seasons, short-term climatic events, tree phenology, accidental or man-made disturbances such as soil amendment).…”
Section: Introductionmentioning
confidence: 99%